PENGARUH TERPAAN MEME POLITIK, KUALITAS INFORMASI DAN LITERASI DIGITAL TERHADAP SIKAP PEMILIH PEMULA DI JABODETABEK - Edy Prihantoro; Winda Widyaningsih; Rizky Wulan Ramadhani (Interaksi: Jurnal Ilmu Komunikasi, 2024)
This study explores the influence of political meme exposure, information quality, and digital literacy on attitude changes among first-time voters in the 2024 election, focusing on Generation Z who utilize social media, particularly Instagram, to seek political information. This information is often presented in various formats, one of which is political memes. The research employs a quantitative approach, distributing questionnaires to 400 respondents across the Greater Jakarta area (Jabodetabek). The data is processed using the Partial Least Squares (PLS) - Structural Equation Modelling (SEM) method through SmartPLS version 4.0 software, consisting of two sub-models: the measurement model (outer model) and the structural model (inner model). The analysis is based on the Stimulus-Organism-Response (SOR) theory. The results indicate that political meme exposure, information quality, and digital literacy significantly affect attitude changes among first-time voters in the 2024 election. Political memes, presented in a light, humorous context, are more easily accepted by first-time voters and thus have a significant impact on their attitude shifts. Political figures, government institutions, and political parties should tailor political information in an accessible and light manner to better engage first-time voters.